2011
DOI: 10.15376/biores.6.1.737-750
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Young’s modulus, morphological, and thermal stability of 5 tropical light hardwoods modified by benzene diazonium salt treatment

Abstract: In this study the tropical light hardwood species jelutong (Dyera costulata), terbulan(Endospermum diadenum), batai (Paraserianthes moluccana), rubberwood (Hevea brasiliensis), and pulai (Alstonia pneumatophora) were treated with benzene diazonium salt to improve their dynamic Young’s modulus (Ed), and thermal stability. Benzine diazonium salt reacted with cellulose in wood and produced 2,6-diazocellulose by a coupling reaction, as confirmed by Fourier transform infrared (FTIR) spectroscopy. Values of Ed were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 22 publications
5
6
0
Order By: Relevance
“…The same phenomenon has also been reported by other researchers [32]. The incorporated major source of this stability is due to the chemical interaction with wood fibers and new chemical bonding, which allows thermal energy to be distributed over many bonds [30].…”
Section: Water Absorption Test Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The same phenomenon has also been reported by other researchers [32]. The incorporated major source of this stability is due to the chemical interaction with wood fibers and new chemical bonding, which allows thermal energy to be distributed over many bonds [30].…”
Section: Water Absorption Test Resultssupporting
confidence: 82%
“…Consequently, the lateral stability of the cell wall was enhanced. Similar results have also been observed by previous researchers [30].…”
Section: Compressive Modulussupporting
confidence: 93%
See 2 more Smart Citations
“…Besides, the FT-IR result also showed the absorption peak of calcite at 875 cm -1 of CO3 2-. This agrees well with the result reported by Islam et al (31) in which they observed the absorption peak of calcite at 875 cm -1 of CO3 2-.…”
Section: General Information For the Catalystsupporting
confidence: 93%